Entr'acte Performing Publics, Pervasive Media, and Architecture - Geiger, J.; Geiger, J. (Avant-Gardes in Performance, 2015)
Generally taking place in front of closed curtains during set changes between acts, the entr'acte delivers a fleeting new purpose and event to the otherwise sometimes inert space between stage and pit. This collection employs the entr'acte as a model for conceptualizing emerging formations of publics and of public space.